Effectiveness of Betahistine in the Management of Vertigo - Ath-Thariq Ramadhan; Ilsa Hunaifi (Unram Medical Journal, 2022)
Vertigo is an illusion of self-movement or environmental movement. This symptom produces some sensation of disorientation in space and is accompanied by vegetative disturbances (nausea, vomiting, sweating) or auditory symptoms (hearing loss, tinnitus, ear fullness). Benign paroxysmal positional vertigo (BPPV), Ménière's disease, and vestibular neuritis are common cases in clinical practice. Treatment of vertigo usually includes the use of medication, physical therapy, and lifestyle adaptations. The most commonly used pharmacological modality is betahistine for the treatment of Ménière's disease and BPPV. Betahistine has activity modulating the histaminergic system, causing vasodilation and improving blood flow to the cochlea, thereby improving vertigo symptoms.